Utilizing Duolingo to Support Vocabulary Mastery for EFL Students: A Systematic Literature Review - Candrika, Ni Putu Sthira; Utami, I G A Lokita Purnamika; Artini, Ni Nyoman (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2025)
Systematic literature review in this study examines the effects of utilizing Duolingo in supporting the improvement of students’ vocabulary mastery in the EFL context by reviewing eleven selected articles that relevant published between 2020 and 2025. The research results indicate that the use of Duolingo has a significant effect on improving students’ vocabulary mastery. In addition, the use of Duolingo can increase students’ motivation learn, improve their writing skills, and provide an enjoyable learning experience. Recommendations for future research regarding the utilization of Duolingo in developing vocabulary mastery of the students include conducting longer-term studies, conducting research in a broader educational context, examining the affective factors experienced by students during implementation, and explore other aspects of language learning.